OF PAKISTAN - F. U. Rahman; F. Perveen; T. Rauf; M. Salim; Z. Ali; S. Khan; Z. Kamal (Journal of Animal and Plant Sciences, 2015)
The present study was conducted to explore the habitat sites occupied by Scotophilus heathii Horsfield, 1831 in two sub- tropical and arid zones of districts Peshawar and Mardan in north western parts of Pakistan. During the present study 514 bats were observed where they were potentially abundant for a period of two years from July 2011 to May 2013. They were observed to fly in the open environment in Syedabad in an old farm house above and an old stagnant water pond provided with a thick vegetation layer, where various arthropods like mosquitoes, moths, and beetles were abundant. A colony (n=347) of S. heathii bats was observed in the cracks in the ceiling of marble factory. The surrounding of this habitat was comprised of many tree species like Acacia, Dalbergia sissoo, Ziziphus jujube, Ziziphus mauritania, Eucalyptus globulus, Morus alba and Morus nigra. While at another habitat about (n=147) bats were observed in the open environment above a small water channel near an old mud made building. They were coming to forage above the stream at a large height. A permanent roost of these bats was found in the ceiling of an old mud made building. This was a diurnal roost, situated near land farms comprised of abundant vegetation and crops like maize, wheat, sugarcane and tobacco. This paper documents new information regarding various habitats occupied by S. heathii to the bats map of Pakistan. A detailed research about their ecology and molecular biology needed to explore potential threats and conservation of the species. several clusters of individuals occupying different
Keywords: Chiroptera; morphology; Charsadda; greater Asiatic yellow bat; Pakistan